MBRS-56. SYSTEMATIC DRUG REPURPOSING IDENTIFIES DIGOXIN AS A DRUG THAT PROLONGS SURVIVAL IN PDOX MODELS OF GROUPS 3 AND 4 MEDULLOBLASTOMA AT CLINICALLY RELEVANT DOSES. Issue 2 (22nd June 2018) - Injac, Sarah; Huang, Lei; Zhao, Hong; Lin, Qi; Kogiso, Mari; Man, Chris; Li, Xiao-nan; Wong, Stephen; Lau, Ching
Abstract: Medulloblastoma (MB) is the most common malignant brain tumor of childhood. While current 5-year EFS is >75 %, recurrent MB continues to have dismal outcomes and survivors face significant treatment-related sequelae. Drug repositioning is a promising strategy which allows for accelerated translation into the clinical setting. To apply this approach to Groups 3 and 4 medulloblastoma, we used a novel algorithm to identify driver signaling pathways by integrating mRNA expression, DNA-copy number, DNA-methylation and DNA-seq profiles from >1, 800 patients. By combining these driver pathways with the targeted effects of 1, 309 drugs from connectivity map database, we identified the cardiac glycoside family of compounds as potential inhibitors of tumor growth. These findings were first validated in MB-derived cell lines which showed high rates of growth inhibition. Patient-derived orthotopic-xenograft (PDOX) models of Group 3 (ICb-2555MB) and 4 MB (ICb-1078MB) were then treated with digoxin (2 mg/kg i.p.) for 2 cycles of 14 days. Digoxin treatment significantly prolonged survival in both models compared to untreated controls (p=0.001; p=0.031). Studies using the Group 3 model further demonstrated that the observed survival benefit is synergistic with radiation. Furthermore, the average digoxin trough levels in treated mice (2.4 ng/mL +/- 0.4) were similar to target levels in patients taking digoxin, suggesting the potential for rapid translation of these findings into a clinical setting. Finally, digoxin-mediated cell killing occurs in vivo via apoptosis and does not require loss of HIF-1 alpha protein.